(untitled) (ALBACORE Jurnal Penelitian Perikanan Laut, 2025)
This study aimed to analyze the performance of environmental, economic, and social conflicts in the utilization of maritime potential, and implement the ICOFISH-MT (integration of coastal fisheries management and marine tourism) model in resolving these conflicts. The method consisted of a descriptive method and the ICOFISH-MT model approach. There were 8 (eight) conflicts in the utilization of maritime potential in the Labuhan Haji Fishing Port Area, divided into 4 environmental conflicts, 3 economic conflicts, and 1 social conflict. The status of 2 conflicts had a limited scale resolution status and 6 conflicts have not been resolved. The implementation of the ICOFISH-MT model in conflict resolution showed that the dominant conflict resolution techniques were negotiation and mediation (75%). The conflict management institution formed had a five-person management consisting of : chairman (1 person), vice chairman (1 person), secretary (1 person), and activities section (2 people). The cooperation scheme to utilize opportunities for integration/synergies of activities from the conflicting parties consisted of 4 profit-based cooperation, 3 non-profit cooperation, and 1 profit and non-profit cooperation. The results of conflict resolution using the ICOFISH-MT model are believed to be able to guarantee the sustainability of maritime potential utilization, increase employment opportunities for fishermen, tourism workers, and the community, and strengthen the role of fishing ports. Key words: conflict resolution, environment, fishing port, fisheries, maritime